OPERASI MILITER SELAIN PERANG (OMSP) TNI UNTUK MENGATASI AKSI TERORISME DALAM PERSPEKTUF HAM DAN PENEGAKAN HUKUM - Putra, Irman; Lubis, Arief Fahmi (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
In the effort to eradicate terrorism, the security dimension is thick in the policy of eradicating terrorism. Civil society is worried about the material of the 2018 Law Number 5 concerning the Eradication of Criminal Acts of Terrorism, it is considered that the Act can reduce the level of state compliance with respect, protection, and fulfillment of human rights in eradicating terrorism, in addition to the effectiveness of the method of eradicating terrorism. The purpose of this study is to provide an overview and analysis of the form of the threat that has undergone a shift that requires the army as the main component of the defense system to reposition itself by placing itself in the right position in the midst of the dynamics of developing threats. The method in this research is normative juridical through a comprehensive study by taking sources from regulations and laws, while empirical juridical research is a study based on observations on threats involving the TNI. The theory used is the Theory of Authority and Theory of Rule of Law as the theoretical basis for the analysis of the main problems regarding the change of the army from a conqueror to a professional soldier. The military does not intervene in politics and conversely there is no political intervention in the military. Law of 2004 Number 34 concerning the TNI states that the Indonesian National Army was built and developed professionally according to the country's political interests, referring to the principles and values of democracy, human rights, civil supremacy, provisions of national and international laws that have been ratified.